Poetry and Philosophy in the Sophists - Allan, William (Araucaria, 2020)
This paper examines the relationship between poetry and philosophy in thesophists, asking what role earlier traditions of poetry and song played in theirwork. The sophists' influence on various genres of literature and philosophyis widely acknowledged, but, as this paper shows, the influence of earliertraditions of poetry and myth on their work was no less important. The paperdemonstrates too how the sophists' engagement with the poetic tradition, likethat of the Presocratics, was geared primarily to serve their philosophical ordidactic goals, even if the aesthetic benefits of poetic language and style werealso appreciated and exploited. Moreover, the sophists recognized poetry'simportant role in education, and their varied use of poetic language, style, andcontent in their own teaching was a continuation of this traditional aspect ofpoetry. In conclusion, the sophists' work on rhetorical, political, and ethicalissues engaged with, and was enriched by, the shared poetic culture of theirtime.